Informal rental housing in the South: dynamic but neglected. (April 2020) - Scheba, Andreas; Turok, Ivan
Informal rental housing is growing rapidly in cities of the global South. Changing needs and circumstances of diverse urban populations produce new forms of rental accommodation and landlord–tenant relations. Focusing on the case of backyard renting in South Africa, this paper illustrates how informal rental is undergoing a dynamic process of expansion and upgrading that both reflects and contributes to improved socioeconomic conditions. Commercialization is transforming the material quality and social dynamics of informal rental housing. While there are signs of formalization and professionalization, the government's neglect of this sector has contributed to the strong persistence of informality, with its associated risks. This paper argues that the informal rental sector deserves more government attention to augment the public benefits and mitigate the costs. The paper ends with suggestions of how a developmental approach by the government could help to convert the negative externalities into a positive dynamic with more equitable and sustainable outcomes.